Undergraduate pre-service EFL teachers’ conceptions of research: a quantitative analysis - Reyes-Cruz, María del Rosario; Rueda de León-Barbosa, Lorgia Isamar; Murrieta-Loyo, Griselda (Colombian Applied Linguistics Journal, 2017)
This study explores the conceptions of research of undergraduate pre-service teachers from an English language major at a public Mexican university from a pragmatist definition of research. A survey design was used. The informants were 108 pre-service EFL teachers of the second, sixth, and tenth semesters of the major. The conceptions of research showed similar percentages among the pre-service teachers in those semesters. Only a slight variation was found in the factor “misconceptions about research.” The factor “research is about problem solving” was the only one that showed a significant but weak correlation with the semester in which undergraduate pre-service EFL teachers were. Slight differences were also found between age range and conceptions of research. The overall lack of differences among the research conceptions of these undergraduate pre-service EFL teachers is opposed to the findings of previous studies. This can be explained by the fact that those studies were done in different contexts and with graduate students from disciplines different from foreign language teaching. It is suggested that students’ misconceptions should be corrected and research activities should be promoted during their studies.